2003
DOI: 10.1177/153331750301800605
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the meaning of everyday life, for those suffering from dementia

Abstract: Living with dementia means struggling to preserve a sense of self, to retain (and reevaluate) one's values in a new situation, and to search for a new way of life. This study explored the meaning of everyday life as expressed by 11 people suffering from dementia. Data were collected through interviews with people in the early stage of a diagnosed dementia disease. The findings indicate that many people with dementia feel shame, sorrow, and sadness when their life with the disease begins but also indicate prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
94
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 18 publications
(16 reference statements)
2
94
0
Order By: Relevance
“…The review of 43 identified studies revealed the following core findings: People with early-stage dementia must deal with many losses-concrete losses, such as losing track of conversations (e.g. Holst & Hallberg, 2003;Phinney & Chesla, 2003); losing track of time (e.g. Nygard & Borell, 1998;Phinney, 1998); forgetting names and events (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of 43 identified studies revealed the following core findings: People with early-stage dementia must deal with many losses-concrete losses, such as losing track of conversations (e.g. Holst & Hallberg, 2003;Phinney & Chesla, 2003); losing track of time (e.g. Nygard & Borell, 1998;Phinney, 1998); forgetting names and events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Devaluing interactions increase this threat (e.g. Holst & Hallberg, 2003;Van Dijkhuizen, Clare, & Pearce, 2006). Memory difficulties may make it difficult for persons with dementia to understand their circumstances or to hide their problems from others, causing frustration, uncertainty, and fear (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People living with dementia become progressively restricted in their performance of daily activities, leading to the need for increased assistance from others in response to their functional losses (Holst & Hallberg, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Access to other health care professionals trained in geriatrics 65,70,73,81,[86][87][88] Need for access to health care professionals who know the disease, respond competently at disclosure of the diagnosis, and communicate test results clearly. Need for help with ADL (commonly for bathing/dental care, dressing, and walking) and with IADL (commonly for housekeeping, meal preparation, and transportation).…”
mentioning
confidence: 99%